Analyzing the applicability of wetland ecological modes in the Minjiang Estuary wetland - Bai, Yuntao; Wang, Lan (Frontiers in Ecology and Evolution, 2024)
Wetlands are badly damaged in many parts of the world. The wetland management of Minjiang Estuary wetland has achieved remarkable results. This provides valuable experience for wetland management in other areas. Minjiang Estuary wetland can achieve the effect, mainly because of the adoption of the water quality management, ecological restoration, and ecological tourism development. However, different management modes have their own scope of application. In order to spread its successes, three differential game modes related to Minjiang Estuary wetland wetland management are constructed, and their equilibrium results are compared and analyzed. Finally, research shows that the amount of water quality control by governments is directly proportional to the resilience of wetlands. The amount of social organization culture is proportional to the degree of better water quality. The amount of development by the government and social organizations is directly proportional to the decrease of investment in the spontaneous tourism industry. When the loss caused by flood or the ecological restoration effect is large, the wetland should adopt the ecological restoration mode. When the increased income or reputation of ecotourism is large, the ecotourism development mode should be adopted. This provides a reference for how to manage wetlands and how to promote the management mode of Minjiang Estuary wetland to other areas more effectively.